Mycoparasitic Trichoderma isolates as a biocontrol agent against Valsa ceratosperma, the causal agent of apple valsa canker - Valetti, Lucio (2022)
Apple valsa canker, caused by the fungus Valsa ceratosperma, is one of the most destructive diseases of this crop. Conventional fungicide treatments are not effective enough; therefore, it is necessary to develop alternatives for the control of this pathogen. The use of Trichoderma strains as a biocontrol agent is a promising strategy for the environmentally friendly management of this disease. In this study, seven different isolates of Trichoderma spp. were obtained from the rhizospheric soil of healthy apple plants. The antagonistic capacity of the isolates against the pathogen V. ceratosperma was evaluated using the dual culture method and by the production of antibiotic non-volatile compounds. In the dual culture method, the interaction zone was observed by differential interference contrast microscopy and confocal laser scanning microscopy. The isolates RN-13, RN-33, and RN-34 inhibited more than 75% of mycelial growth, whereas RN-19, RN-16, and RN-15 inhibited growth by 65–72% with respect to the control. The mycoparasitic activity was evidenced by the coiling of hyphae around pathogen hyphae, appressorium-like structures, morphological deformations, and disintegration of mycelial walls. Apple shoots inoculated with Trichoderma isolates and then infected with V. ceratosperma showed the antagonist capacity of RN-16, RN-19, RN-15, and RN-18, which produced a significant decrease in the size of the lesion. Overall, the results showed the great potential of Trichoderma as a biocontrol agent against apple tree valsa canker. Further studies of this fungal interaction are required to design effective control strategies for the protection of apple tree orchards from this disease.